2015
DOI: 10.1007/s11482-015-9426-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Recycling Behaviour in High-Rise Buildings: A Case in Hong Kong

Abstract: Many researchers, environmentalists and economists have made tremendous efforts to enable polices and measures for waste recycling, to improve the quality of the public living environment and to achieve a better quality of everyday life. This study examined the quality of life (QOL) in high-rise buildings in relation to sustainability. It investigated household recycling behaviour and explored the QOL factors that affect such behaviour. Two models based on different types of recycling behaviour were estimated:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Few studies focus on recycling behaviour in relation to specific housing types. Some of these have examined recycling amongst Asian-British residents in terraced housing [10], recycling in multi-family residential buildings in the UK, US, and Canada [11][12][13], medium-and high-density housing in the UK [14], high-rise buildings in Hong Kong [15] and single-versus double-storey houses in Malaysia [16]. These studies suggest that less affluent households and households living in higher-density settings recycle less compared to more affluent households and households living in lower-density settings.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies focus on recycling behaviour in relation to specific housing types. Some of these have examined recycling amongst Asian-British residents in terraced housing [10], recycling in multi-family residential buildings in the UK, US, and Canada [11][12][13], medium-and high-density housing in the UK [14], high-rise buildings in Hong Kong [15] and single-versus double-storey houses in Malaysia [16]. These studies suggest that less affluent households and households living in higher-density settings recycle less compared to more affluent households and households living in lower-density settings.…”
Section: Introductionmentioning
confidence: 99%
“…(Silva et al, 2008 ) 84.62% Examining the association between body mass index and weight related quality of life in black and white women (Cox et al, 2012 ) 84.06% Relationship between morbidly obese subjects' attributions of low general well-being, expectations and health-related quality of life: Five-year follow-up after gastric banding (Pristed et al, 2012 ) 82.59% Alcohol and Quality of Life Among Social Groups for the Elderly in São José dos Campos, Brazil (Santos et al, 2014 ) 79.65% 11. Community Issues Social trust and health: A perspective of urban–rural comparison in China (Jiang et al, 2020 ) 91.71% Quality of life and recycling behaviour in high-rise buildings: A case in Hong Kong (Siu & Xiao, 2016 ) 90.51% Evaluation of life quality and its spatial mismatch with local economic development in large Chinese cities (Zeng et al, 2020 ) 88.42% Patterns of walking among employed, urban Canadians: Variations by commuting mode, time of day, and days of the week (Michelson & Lachapelle, 2016 ) 86.74% Assessment of socio-economic characteristics and quality of life expectations of rural communities in Enugu State, Nigeria (Nzeadibe & Ajaero, 2010 ) 86.59% 12. Health-related QoL (HRQoL) II Comorbid social phobia and major depressive disorder: The influence of remission from depression on quality of life and functioning (Steiner et al, 2017 ) 92.11% Quality of life in patients with recurrent vasovagal or unexplained syncope: Influence of sex, syncope type and illness representations (St-Jean et al, 2008 ) 91.36% The association between post-traumatic stress and health-related quality of life in adults treated for a benign meningioma (Kangas et al, 2012 ) 91.05% Pychological factors associated with a better quality of life following hea...…”
Section: Resultsmentioning
confidence: 99%
“…Different from cities with low population densities, the particular high-rise and high-density living situation in Hong Kong has brought many challenges to FWR. Studies of waste recycling have indicated that it can be difficult to conduct recycling projects without understanding living environments and specific lifestyles (Martin et al, 2006;Siu and Xiao, 2016).…”
Section: Identifying Contextual Factorsmentioning
confidence: 99%